On an alternative solution to the TR switch - Woodman Pollitt, Ronald Francisco (1976)
An alternative solution is presented for the design of the transmitreceive switch making use of the high power 3-dB-directional couplers which would be used in the SOUSY antenna. The system presents sorne advantages and may be worth to evaluate its performance in parallel with the present approach, (The diodes could be replaced for evaluat ion of the scheme by their equivalent network to avoid delays due to delivery of the parts.